Research Progress on Mechanoenzymatic Reactions - CUI Tianyu, XIN Jiaying, SUN Lirui, LI Yue, LIU Jingxue, ZHANG Jianxiong, XIA Chungu (Shipin Kexue)
In recent years, in the context of global resource shortage, mechanoenzymatic reactions have attracted great attention from both academia and the food industry due to their efficient, green, energy-saving and sustainable characteristics. Organic synthesis reactions typically use a large amount of chemical reagents and require strict reaction conditions and complex downstream operations to separate and purify products, which should be used sparingly or not at all in foods. Mechanoenzymology, i.e., the use of mechanical energy to promote enzyme-catalyzed reactions in a solvent-free system, is in line with the current development needs and concepts. This paper reviews the origin, development, influencing factors and mechanism of mechanoenzymology and the applications of different enzymes in mechanoenzymology in order to provide theoretical guidance for the field of food chemistry and biocatalysis.